An Efficient One-Pot Three-Component Synthesis of Novel Sulfanyl Tetrazoles Using Ionic Liquids - Sankari Kanakaraju; Bethanamudi Prasanna; G. V. P. Chandramouli (Journal of Chemistry)
An efficient, simple, and environmentally benign method for the synthesis of novel sulfanyl tetrazoles has been achieved by one-pot three-component reaction of phenacyl bromides/3-(2-bromoacetyl)coumarins with KSCN and NaN3 using [Bmim]BF4 ionic liquid. It could be reused and recycled for four runs without significant loss of product yield.